The synthesis of amino-functionalized carbon quantum dots-decorated hydroxyapatite as drug delivery agent - Hui, Khee Chung; Dhanapalan, Nagaammai; Khayrani, Apriliana Cahya; Imanto, Teguh; Sambudi, Nonni Soraya (Comptes Rendus. Chimie)
Hydroxyapatite (HAp) was combined with amino-functionalized carbon quantum dots (CQDs) to enhance the optical and surface area properties of HAp. The loading of amino-functionalized CQDs could enhance the luminescence of HAp and its UV–Vis absorbance. Additionally, surface area of HAp could be increased from 84.16 to 129.94 m$^{2}$/g by loading amino-functionalized CQDs. The drug release experiment was conducted using acetaminophen. The release happened slowly for amino-functionalized CQDs/HAp, with full release of acetaminophen being observed after 24 h. The enhanced luminescence composite shows high potential for the composite to be used for the controlled release of drugs.